Changes in the BTK/NF-κB signaling pathway and related cytokines in different stages of neuromyelitis optica spectrum disorders - Huimin Qiao; Zhuofeng Mao; Wei Wang; Xin Chen; Suhuan Wang; Haolong Fan; Tianyi Zhao; Huiqing Hou; Mei Dong (European Journal of Medical Research, 2022)
Abstract Objective Neuromyelitis optica spectrum disorders (NMOSDs) are blindness-causing neuritis; their pathogenesis is still not fully elucidated. Although it has been determined that Bruton tyrosine kinase (BTK) and NF-κB are associated with NMOSD, the changes that occur in different periods remain unknown. The study aimed to demonstrate the changes in the BTK/NF-κB pathway and related chemokines in different stages of NMOSDs. Methods A total of 32 patients with NMOSD were selected as the experimental group, and 32 healthy volunteers were included in the control group. In this study, the BTK/NF-κB pathway and related chemokines in the cerebrospinal fluid and peripheral blood samples of patients with NMOSD were analyzed in the acute or remission phase. Results BTK, NF-κB, PI3K, IKK, CXCL2, and CXCL12 levels in the NMOSD group in the acute or remission phase were significantly higher than those in the control group (p < 0.05). Conclusion The BTK/NF-κB pathway plays a vital role in the progression of NMOSD pathology. Our results shed light on its important role as a therapeutic target for NMOSD.